Internet‐delivered eating disorders prevention program for adolescent girls with type 1 diabetes: Acceptable and feasible. Issue 7 (12th August 2022) - Trojanowski, Paige J.; Frietchen, Rachel E.; Harvie, Blair; Mehlenbeck, Robyn; Fischer, Sarah
Abstract: Background: Adolescents with type 1 diabetes are at significantly increased risk for eating disorders and few interventions exist. Objective: This study examined the feasibility, acceptability, and preliminary effects of an internet‐based eating disorders prevention program adapted specifically for adolescent girls with type 1 diabetes. Participants and Methods: Thirty‐five girls (16.2 ± 1.1 years) participated Body Project (T1D Style), a 4‐week program consisting of four adolescent sessions focused on promoting illness acceptance, challenging sociocultural body image pressures, increasing social support, and teaching assertive communication. Caregivers participated in one session focused on fostering body image positivity and a healthy relationship with food. Pre‐intervention, post‐intervention, and 3‐month follow‐up surveys assessed disordered eating, body dissatisfaction, thin‐ideal internalization, diabetes acceptance, diabetes distress, and quality of life. Cohen's d effect sizes were calculated at post‐intervention and follow‐up. Program acceptability was assessed at post‐intervention. Manual fidelity and homework completion were monitored. Results: High manual fidelity, retention, and homework completion were achieved. Quantitative and qualitative feedback from teens and caregivers suggested high acceptability. Large effects ( d  = 1.35–0.83) were observed for dieting, body dissatisfaction, diabetes distress, diabetes acceptance, and diabetes‐related quality of life at post‐intervention, with large‐medium effects ( d  = 1.16–0.58) at follow‐up. Medium‐small effects ( d  = 0.49–0.78) at post‐intervention were observed for diabetes‐specific disordered eating and thin‐ideal internalization, with effects maintained at follow‐up. Conclusions: Results support the acceptability and feasibility of this targeted eating disorders prevention program for adolescent girls with type 1 diabetes. Future clinical trials are warranted to determine its effectiveness compared to a control condition.